Sexual Activity After Acute Coronary Syndrome: A Qualitative Approach to Patient and Partner Experiences. Issue 5 (September 2021) - Boothby, Célina A.; Santana, Maria J.; Norris, Colleen M.; Campbell, Tavis S.; Rabi, Doreen M.
Abstract : Background: Little is known about how best to support both patients and their partners in the reengagement of sexual activity (SA) after acute coronary syndrome (ACS), with sparse direct data from the partner on their needs and concerns in the area of SA support. Objectives: We undertook a qualitative study to address this gap in the literature through 3 objectives from a patient and partner perspective: (1) to characterize the experience of reengaging in SA post ACS, (2) to identify needs and priorities in the area of SA support post ACS, and (3) to determine whether cardiac rehabilitation (CR) could be an acceptable point of intervention for SA support. Methods: Semistructured qualitative interviews were conducted with 6 male patients who were post ACS and their partners (age range, 47–81 years). Patients were criterion sampled from the Alberta Provincial Project for Outcome Assessment in Coronary Heart Disease database. Inductive thematic data analysis was conducted. Results: Four themes were identified: "importance, " "support received, " "on their own, " and "wanting support." Couples reaffirmed the importance of SA pre and post ACS, reported SA support as currently insufficient but articulated ways it could be improved, and reported CR as a current source of SA support but thought there could be room for improvement on the content and delivery of such information. Conclusions: This study illustrates the potential value of promoting SA support for both patients who are post ACS and their partners and reports that SA support provided at CR would be viewed as important, needed, and acceptable.